Harnessing Korean English Leaners’ Funds of Knowledge through Culturally Responsive Readings - Kim, Sung-ae (International Journal of Language and Literary Studies, 2024)
The intersection of language learning and the construction of authentic meaning by bilinguals through culturally responsive reading activities remains relatively underexplored in academic discourse. Moreover, prevailing instructional methodologies often fail to fully leverage the linguistic and cultural assets that English Learners (ELs) bring to their educational experiences. This study adopts a case study approach to investigate the responses of two Korean ELs as they interact with culturally responsive texts, drawing upon their rich funds of knowledge and employing a specific reading strategy within their learning process. Given the dearth of research on the impact of culturally responsive texts on ELs’ literacy learning, particularly within the context of Korean ELs, this study offers a nuanced examination of the reading experience and language learning of two individuals from this demographic. Data collection includes direct classroom observations and video recordings from the Korean Heritage Language (HL) school. The findings underscore the proficiency of ELs in leveraging their funds of knowledge during retelling activities, enabling Korean ELs to personalize and internalize the text. By showcasing the effectiveness of these practices in shaping meaningful reading experiences, this study offers valuable insights into instructional practices in literacy and language education for ELs.